Polypharmacy among patients with multiple sclerosis: a qualitative systematic review. Issue 2 (1st February 2020) - Frahm, Niklas; Hecker, Michael; Zettl, Uwe Klaus
ABSTRACT: Objectives : The consequences of polypharmacy (intake of ≥ 5 drugs) are diverse, including drug interactions, rising costs and side effects. Risk groups for polypharmacy are multimorbid and chronically ill people, such as patients with multiple sclerosis (MS). MS is the most common neuroimmunological disease in young adults worldwide. We aimed to provide a systematic overview of the current research status regarding frequency and predictors of polypharmacy in MS patients. Methods : A systematic literature search in the databases PubMed, Cochrane Library and Scopus was carried out according to the PRISMA guidelines. English and German original research articles were included. Results : Seven studies fulfilled the inclusion criteria of this review, while the research objectives and methods were very heterogenous. The polypharmacy rates in these studies ranged from 15% to 59%. Polypharmacy correlated with comorbidities, increased disability, cognitive deficits, increased hospitalization, higher relapse rate and lower quality of life. Conclusions : In MS patients, polypharmacy is common and closely associated with health issues. There is a great need for research in this area, especially regarding longitudinal changes in drug utilization. Effective networks between physicians and pharmacists are needed to optimize medication management for patients and to achieve the best possible therapy results.